ON THE FORM OF THE SOLUTION OF ONE SECOND ORDER DIFFERENTIAL EQUATION WITH FUNCTIONAL COEFFICIENTS - Dimov, Lazo A. (Matematichki Bilten, 2011)
In this work about the differential equation (2) we determine the circumstances in which we can transforme it in differential equation in the form (1) and then with the formulas (2’), (3’) and (4’) we determine its solution.